Biocryoimmunology — a new scientific revelation in bioscience and medical practice - Nahrebetskyi, Volodymyr; Prytkov, Fedir; Tsurikova, Oksana; Korpan, Nikolai (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):229